MORALITY THROUGH INQUIRY, MOTIVE THROUGH RHETORIC: THE POLITICS OF SCIENCE AND RELIGION IN THE EPOCH OF THE ANTHROPOCENE: with Mark Harris, "'The People of This Country Have Had Enough of Experts': In Defense of the 'Elites' of the Science‐and‐Religion Debate"; Fern Elsdon‐Baker, "In Defense of Publics: Projection, Bias, and Cultural Narratives in Science and Religion Debates"; Elaine Howard Ecklund, Sharan Kaur Mehta, and Daniel Bolger, "A Way Forward for Sociological Research on Science and Religion: A Review and a Riff"; Nathan Crick, "Morality through Inquiry, Motive through Rhetoric: The Politics of Science and Religion in the Epoch of the Anthropocene"; and John H. Evans, "The Scope and Implications of Morals Not Knowledge.". Issue 3 (19th August 2019) - Crick, Nathan
Abstract: In an epoch marked by the threat of global warming, the conflicts between science and religion are no longer simply matters that concern only intellectual elites and armchair philosophers; they are in many ways matters that will determine the degree to which we can meet the challenges of our times. John H. Evans's Morals Not Knowledge represents an important provocation for those committed not only to using scientific method as a resource for making moral judgments but also to creating political alliances with religious constituencies. In this important work, Evans argues that most conflicts between science and religion do not concern a clash between two contradictory ways of knowing, but rather a clash over our moral responsibilities and ultimate values. In my response to his work, I suggest that integrating both John Dewey's pragmatic understanding of the moral situation and Kenneth Burke's rhetorical interpretation of motives helps bolster Evans's cause and provides support for a political movement that aims to bridge the divide between science and religion in the epoch of the Anthropocene.